Spatial and temporal variation patterns in aquatic macroinvertebrates of Tecocomulco Lake, Hidalgo (México) - Rico-Sánchez, Axel Eduardo; Rodríguez-Romero, Alexis Joseph; López-López, Eugenia; Sedeño-Díaz, Jacinto Elias (Revista de Biología Tropical, 2014)
Lake Tecocomulco, Hidalgo, is a relic of the ancient lakes of Anahuac, important for the conservation of resident and migratory birds. However, the composition of aquatic macroinvertebrates is unknown; this is an important gap in conservation as they play an important role in the food web. This study analyzed the spatial and temporal variations in macroinvertebrate assemblages and their relationship with habitat characteristics. We carried out four monitoring campaigns covering the rainy and dry seasons. The monitoring was conducted at six study sites (four in the littoral zone and two in the middle part of the lake), environmental factors were recorded at each study site, water samples were collected for their physical and chemical analysis and aquatic macroinvertebrates were collected. A principal component analysis (PCA) was used to group study sites based on physical and chemical characteristics. Richness of taxa was analysed with rarefaction. We assessed the importance value index of each taxon (considering their frequency of occurrence and abundance). Similarity analyzes were performed between study sites and similarity of taxa with indices of Jaccard and Bray-Curtis, respectively. We performed a canonical correspondence analysis (CCA) between environmental factors and macroinvertebrate taxa. The PCA showed a marked seasonal variation represented by warm periods, with high values of conductivity, alkalinity, hardness, sulfates, and macronutrients (N and P) and the cold period with low values. We found a total of 26 taxa of aquatic macroinvertebrates and the highest richness was found in August. The Jaccard similarity analysis found differences between the littoral area and the limnetic zone, which differ also in the composition of macrophytes. The littoral zone had the highest taxa richness of macroinvertebrates and macrophytes, while the lowest diversity was found in the offshore zone. The CCA related physicochemical characteristics of the water body with macroinvertebrate taxa showing the influence of both physicochemical characteristics and the composition of macrophytes in the spatio-temporal patterns of aquatic macroinvertebrates in the lake. The dominance of Corixidae highlights a strong grazing activity in the lake and in turn suggests an important amount of food available for higher trophic levels. Our study shows that the macroinvertebrates of Tecocomulco Lake have spatial and seasonal variations that are related to both environmental and biotic factors with groups being dominant. Rev. Biol. Trop. 62 (Suppl. 2): 81-96. Epub 2014 April 01.